The Effect of Combined Administration of Sea Urchin Gonad and Aloe Vera Suspension on the Enhancement of Macrophage Phagocytosis Activity in Male White Rats Induced by Salmonella Typhimurium - Adi Saputro; Aima Ifanna Puteri; Sandra Dewi Arini; Gilang Rizki Al-Farizi; Fransisca Gloria; Ovikariani Ovikariani (Pelopor Publikasi Akademika, 2023)
This research determined the influence of the administration of combined gonadal sea urchin suspension and aloe vera to improve the macrophage phagocyte activities of male mice (Rattus norvergicus). This experimental laboratory research used a posttest-only control group design with white mice (Rattus norvegicus). The researcher grouped the mice into three groups: the negative control group with CMC-Na (0,5% /kg Weight); the positive group with Levamisole 0,9 mg/ 200 weight; and the intervention group with combined gonadal sea urchin suspension, Tripeneustes gratila, with a dose of 2,2700g/kg Weight, and the extracted aloe vera for 15ml. The researcher provided the treatment for 12 days, orally, twice a day with the induction of Salmonella typhimurium of 104 CFU 0,1 ml on the fifth day. The outcome of the macrophage phagocyte capability on the thirteenth day was calculated with the phagocytes index. The One-Way Anova test of gonadal sea urchin suspension, Tripneustes gratila with a dose of 2.2700 g/kg Weight with the extracted aloe vera indicated the highest phagocytes index, 2.28 (p<0.05) than the control group. The combined gonadal sea urchin suspension, Tripneustes gratilla, with the extracted aloe vera could improve the macrophage phagocyte activities.